Enhancing heat transfer performance of a two-phase closed thermosyphon using a polymer-coated hydrophobic condenser - Seo, Donghyun; Park, Jinsoo; Shim, Jaehwan; Nam, Jeonghyeon; Shin, Dong Hwan; Nam, Youngsuk; Lee, Jungho (Applied Thermal Engineering, 2021)
A two-phase closed thermosyphon (TPCT) is a passive heat transfer device that transfers heat from one point to another by two-phase fluid circulation. Dropwise condensation on a hydrophobic surface, where discrete droplets grow on a condenser surface, promises higher condensation heat transfer coefficients (≈40–70 kW/m2⋅K) than conventional filmwise condensation. Recent researchers have investigated the effect of dropwise condensation on the heat transfer performance of a TPCT. However, their measured condenser heat transfer coefficients (<25 kW/m2⋅K) were much lower than expected, and the heat transfer enhancement mechanism of a hydrophobic TPCT has not been investigated in depth. Here, we achieved a higher condenser heat transfer coefficient of ~66 kW/m2⋅K in a TPCT using a polymer-based hydrophobic coating film and investigated the heat transfer enhancement mechanism by performing experiments and analytical models. A thin polymer film with an optimized thickness (≈60 nm) was combined with adhesion promoter layers to achieve stable and high-performance dropwise condensation consisting of enhanced surface roughness and a coupling agent. The internal two-phase flow patterns and condensation behaviors were systematically evaluated for the heat transfer performance, which was compared to untreated bare and CuO nanostructured superhydrophobic surfaces. We revealed that rapid droplet removal and active re-nucleation on the polymer-coated hydrophobic surface in a TPCT led to 6 times higher condenser heat transfer coefficients and 68–74% smaller overall thermal resistance than those of the bare and superhydrophobic TPCTs. These results are helpful to understand the effect of dropwise condensation on the heat transfer performance of a TPCT and provide a direction for developing more efficient TPCTs.
Keywords: Condenser heat; Dropwise condensation; Heat transfer enhancement mechanism; Heat transfer performance; Heat-transfer coefficients; Hydrophobic surfaces; Hydrophobics; Thermal; Thermosiphon; Two-phase closed thermosyphon; Condensation; Heat pipe; Heat transfer; Hydrophobic; Thermal resistance; Thermosyphon